2000
DOI: 10.1016/s0042-6989(99)00241-2
|View full text |Cite
|
Sign up to set email alerts
|

Weighted directional energy model of human stereo correspondence

Abstract: Previous work [Prince, S. J. D, & Eagle, R. A. (1999). Size-disparity correlation in human binocular depth perception. Proceedings of the Royal Society: Biological Sciences, 266, 1361-1365] has demonstrated that disparity sign discrimination performance in isolated bandpass patterns is supported at disparities much larger than a phase disparity model might predict. One possibility is that this extended performance relies on a separate second-order system [Hess, R. F., & Wilcox, L. M. (1994). Linear and non-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 49 publications
2
33
4
Order By: Relevance
“…At each disparity value the populations were tested with 40 stimuli (20 positive and 20 negative disparities). Open triangles depict performance for 0.8 cycles/ deg Nyquist frequency, solid triangles depict performance for 3.0 cycles/deg Nyquist frequency to linear combinations (Fleet et al 1996;Qian and Zhu 1997;Prince and Eagle 2000b). By contrast, information contained in a population response was extracted with an optimal and unbiased maximum-likelihood estimator (Oram et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At each disparity value the populations were tested with 40 stimuli (20 positive and 20 negative disparities). Open triangles depict performance for 0.8 cycles/ deg Nyquist frequency, solid triangles depict performance for 3.0 cycles/deg Nyquist frequency to linear combinations (Fleet et al 1996;Qian and Zhu 1997;Prince and Eagle 2000b). By contrast, information contained in a population response was extracted with an optimal and unbiased maximum-likelihood estimator (Oram et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…DeAngelis et al (1998) demonstrated that stimulation in area MT influences depth perception in the macaque monkey. In a theoretical study, Prince and Eagle (2000b) investigated the performance of a physiologically motivated model under several psychophysical tasks. They found effects formerly attributed to a postulated but yet unknown second nonlinear stereochannel and could thereby partly reconcile properties of the neurons with psychophysical data.…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways in which the output of the energy model may contribute to the estimation of disparity (see Fleet et al 1996b;Prince and Eagle 2000). Because the calculation is performed over a limited area (the RF), there will always be circumstances in which false matches can produce substantial correlations.…”
Section: What Do Disparity-selective Cells In V1 Calculate?mentioning
confidence: 99%
“…This has been used widely (e.g., Fleet et al 1996a,b;Prince and Eagle 2000;Qian 1994;Qian and Zhu 1997) since its inception and will be referred to here as "Gabor energy model." All experimental data used to assess its validity (Anzai et al 1999a(Anzai et al ,b, 1997DeAngelis et al 1995;Ohzawa and Freeman 1986a,b;Ohzawa et al 1990Ohzawa et al , 1996Ohzawa et al , 1997 have been gathered from V1 neurons in the anesthetized cat using one-dimensional stimuli (bars or gratings).…”
Section: Introductionmentioning
confidence: 99%
“…Although several physiologically-based models have been proposed (Fleet et al, 1996;Grossberg, 1994;Grossberg and Howe, 2003;Lehky and Sejnowski, 1990;Lippert and Wagner, 2002;Matthews et al, 2003;McLoughlin and Grossberg, 1998;Mikaelian and Qian, 2000;Prince and Eagle, 2000;Qian, 1994Qian, , 1997Qian and Andersen, 1997;Read, 2002a,b;Tsai and Victor, 2003;Watanabe and Idesawa, 2003;Zhaoping, 2002), much work remains to be done in tying these theories more closely to the known physiology, and expanding them to provide a complete account of stereoscopic perception.…”
Section: Outstanding Questionsmentioning
confidence: 99%